2008
DOI: 10.1093/carcin/bgn218
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane vesicles enhance the carcinogenic potential of Helicobacter pylori

Abstract: Chronic Helicobacter pylori infection is associated with an increased risk of gastric carcinogenesis. These non-invasive bacteria colonize the gastric mucosa and constitutively shed small outer membrane vesicles (OMV). In this study, we investigated the direct effect of H.pylori OMV on cellular events associated with carcinogenesis. We observed increased micronuclei formation in AGS human gastric epithelial cells treated with OMV isolated from a toxigenic H.pylori strain (60190). This effect was absent in OMV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 57 publications
0
70
0
4
Order By: Relevance
“…We and others have previously shown that H. pylori OMV are internalized by gastric epithelial cells (8,15,44,45). In this study, we sought to examine the rate and mechanism of OMV internalization using the lipophilic fluorescent membrane dye DiO to monitor OMV localization.…”
Section: Assessment Of the Rate Of H Pylori Omv Internalization By Amentioning
confidence: 86%
See 1 more Smart Citation
“…We and others have previously shown that H. pylori OMV are internalized by gastric epithelial cells (8,15,44,45). In this study, we sought to examine the rate and mechanism of OMV internalization using the lipophilic fluorescent membrane dye DiO to monitor OMV localization.…”
Section: Assessment Of the Rate Of H Pylori Omv Internalization By Amentioning
confidence: 86%
“…However, despite the ability to adhere to the gastric epithelium, the majority of organisms remain unattached to surface cells (32), leading to speculation that lipopolysaccharide (LPS)-enriched outer membrane vesicles (OMV) shed by these bacteria (15,19,26) contribute to H. pylori pathogenesis via the persistent delivery of bacterial virulence factors (including the vacuolating cytotoxin VacA) and antigens to the gastric mucosa (26,27). Observations that H. pylori OMV modulate gastric epithelial cell proliferation (22), induce apoptosis (3), stimulate secretion of the proinflammatory cytokine interleukin-8 (22), increase micronucleus formation (8), and are at the luminal surface (15,26) and within cells of the gastric epithelium (15) support this hypothesis.…”
mentioning
confidence: 99%
“…OMVs contribute in bacterial pathogenesis because adhesins, toxins and immunomodulatory compounds have been identified as OMV cargo (Figure 1) (Grenier and Mayrand, 1987;Kadurugamuwa and Beveridge, 1995;Horstman and Kuehn, 2002;Wai et al, 2003;Kesty et al, 2004;Chitcholtan et al, 2008). Heat labile enterotoxin (enterotoxigenic E. coli), VacA (Helicobacter pylori), Shiga toxin (Shigella dysenteriae and enterohemorrhagic E. coli) and ClyA (enterohemorrhagic E. coli) are some examples of the several toxins that have been reported to be associated with OMVs (Horstman and Kuehn, 2000;Horstman and Kuehn, 2002;Wai et al, 2003;Dutta et al, 2004;Kesty et al, 2004;Chitcholtan et al, 2008).…”
Section: Roles In Pathogenesismentioning
confidence: 99%
“…Heat labile enterotoxin (enterotoxigenic E. coli), VacA (Helicobacter pylori), Shiga toxin (Shigella dysenteriae and enterohemorrhagic E. coli) and ClyA (enterohemorrhagic E. coli) are some examples of the several toxins that have been reported to be associated with OMVs (Horstman and Kuehn, 2000;Horstman and Kuehn, 2002;Wai et al, 2003;Dutta et al, 2004;Kesty et al, 2004;Chitcholtan et al, 2008). Also, the enteric pathogen, Salmonella typhi was shown to induce hemolysin packing into OMVs in response to norepinephrine (Karavolos et al, 2011).…”
Section: Roles In Pathogenesismentioning
confidence: 99%
“…Cancer has traditionally been considered as a human disease resulting from gene mutations but new finding suggest that extracellular vesicles which are derived from tumour can carry polypeptides, polysaccharides, DNA and RNA causative of cancer progression [151]. Intake of the tumor derived extracellular vesicles (EVs) by non-tumor cells can be converted into cancerous cell [152]. EV released by cancer cells also acts against the stress response [93].…”
Section: Extracellular Vesicles (Ev) Proteomics In the Study Of Humanmentioning
confidence: 99%